Serum Glucose Level According to Menstrual Cycle Phases in Young Students at the College of Science for Women - Ghadeer Hamid AL-Ardhi1 , Noran Jameel Ibraheem2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: This study was carried out to present data on serum fasting glucose level in healthy young women with regular menstrual cycle who have moderate active state across their three different stages of the menstrual cycle (menstruation, proliferation and secretory) phases. Subjects and Method: A total of 50 non-diabetes women with normal regular menstrual cycle were involved in this study, the subjects ages ranged from 20-24 years, fasting venous blood (3ml) was collected at early morning during menstruation phase (days 1-5), proliferation phase (6-14 days) and the secretory phase (15- 28days) for each subject, serum glucose measurement were conducted by colorimetrictechnique. Results: The present study shows non-significant (p<0.05) increase in the mean of glucose level during menstruation and proliferative phase (92.8±12.7, 92.6±10.2 mg/dl) respectively in the same subject comparison with secretory phase (90.48±8.3mg/dl) in the same subject. Conclusion: This study revealed that serum glucose level does not change along stages of normal and regular menstrual at rest or moderate active young women.